The Language Growth of Spanish‐Speaking English Language Learners. Issue 2 (17th October 2012) - Rojas, Raúl; Iglesias, Aquiles
<x xml:space="preserve">Abstract</x> Although the research literature regarding language growth trajectories is burgeoning, the shape and direction of English Language Learners' (ELLs) language growth trajectories are largely not known. This study used growth curve modeling to determine the shape of ELLs' language growth trajectories across 12, 248 oral narrative language samples (6, 516 Spanish; 5, 732 English) produced by 1, 723 ELLs during the first 3 years of formal schooling (M age at first observation = 5 years 7 months). Results indicated distinct trajectories of language growth over time for each language differentially impacted by summer vacation and gender, significant intra‐ and interindividual differences in initial status and growth rates across both languages, and language‐specific relations between language growth and initial status. Implications of ELLs' language growth are discussed.